2022
DOI: 10.1155/2022/4313394
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Thrombelastography in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease and the Relationship with Lung Function

Abstract: Purpose. To analyze the changes in thrombelastography (TEG) in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and the relationship with indicators related to lung function. Methods. 100 patients with AECOPD admitted to our hospital from May 2021 to May 2022 were selected as the AE group, and another 80 patients with a stable phase of COPD in the same period were selected as the SP group. Fresh blood specimens were collected from both groups, and TEG-related indicators (R val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%